A Life Lived Across Continents: The Global Microhistory of an Armenian Agent of the Compagnie des Indes Orientales, 1666–1688. Issue 1 (March 2018) - Aslanian, Sebouh David
Abstract : In 1666, French finance minister Jean-Baptiste Colbert hired Martin di Marcara Avachinz, an Armenian merchant who had lived in Iran and India, as an agent for his newly established Compagnie des Indes orientales. In 1669, shortly after the Armenian had secured a royal edict from the sultan Of Golconda to set up a French trading center in the port of Masulipatam, he was summarily arrested, tortured, and sent to France by his superior François Caron. This article provides a close reading of the legal briefs or factums produced during the sensational trial that followed Marcara's release from prison in 1675. In tracing a "global microhistory" of his life across continents, it seeks to contribute to a deeper understanding of early modern long-distance trade in the Indian Ocean, comparing the network of the CIO and other joint-stock corporations with the "stateless" nature of the trade diaspora of Armenian merchants from the township of New Julfa on the outskirts of the Safavid capital Isfahan. Finally, the article considers the role of factums in early modern France and explores how the "exceptionally normal" story of Marcara's life provides a useful window onto French perceptions of the Orient and the fear induced by communities such as Armenian and Indian merchants, bankers, and brokers.